In vitro shear and compression protocols to evaluate the effects of oral processing on purées intended for dysphagia patients - Kovan Ismael-Mohammed; Laura Laguna; Mireia Bolivar-Prados; Pere Clavé; Amparo Tarrega (Applied Food Research, 2025)
Bolus viscosity before swallowing is critical in dysphagia patients. Only a few works have assessed this viscosity using real boli expectorated by humans. However, this may be a risk for dysphagia patients, and it could be avoided by using an in vitro method to mimic oral changes. This study evaluates the feasibility of two in vitro protocols: (i) constant shearing (50 s⁻¹) over 120 s using a rheometer, and (ii) uniaxial force (10 strokes at 10 mm/s) using a texture analyzer, and then comparing it with previous human data. For both systems, the effect of dilution and enzymes (artificial saliva) was also studied by calculating the percentage of reduction. Results showed that only constant shear decreased the purees viscosity at 20 s from 10 % to 28 % and even more at 120 s (between 30 %-85 %). This viscosity was further reduced in the condition shear and water, and even more in the condition shear and saliva. The uniaxial compression results showed a similar trend: the addition of water caused smaller changes than the addition of saliva in both maximum force (7–38 %) and adhesiveness (62–75 %). Among the two in vitro systems, the constant shear led to a greater structural breakdown, simulating the most extreme scenario of viscosity reduction that could occur during oral processing. Texture analyzer protocol allows a continuous saliva addition, movement to mimic oral stroke and it provides adhesiveness values. Constant shear produced a structural breakdown pattern more similar to human boli than axial force.